3D modeling of the anterior segment of the human eye from OCT images - Foo, Shi Kai. (2013)
Asians are exposed to one of the two most typical types of glaucoma in the world, primary angle-closure glaucoma (PACG). This is due to the fact that Asians may be physically inclined to PACG. In Asian eyes, the iris (the colored part of the eye) attaches to the sclera (the eye’s white, protective covering) in such a way as to form a more physically confined angle with less trabecular meshwork exposed. PACG is approximated to become an increasing problem as the world faces an aging population. Furthermore, it will amplify the economic burden on the society. In this project, angle-closure glaucoma (ACG), which is an emergency condition of PACG, where the fluid in the eye is completely cut off, is used to study the effect that glaucoma has on the shape and stress of the human eye. Finite Element Method (FEM) had been used for quantitative modelling and simulating on human anterior chamber segment anatomy, the results proved the practicability, competency and precision of this method. A 3D model was constructed and presented in this report. Firstly, four images acquired using optical coherence tomography (OCT) are used to extract the 2D coordinates of the contour of the human eye and then transformed into 3D coordinates in Matlab. After which, a 3D model was constructed using the 3D coordinates obtained and simulations were conducted to determine the effects it has on the shape of the eye in ANSYS 14.0.